The anti-fungal effect of miconazole and miconazole-loaded chitosan nanoparticles gels in diabetic patients with Oral candidiasis-randomized control clinical trial and microbiological analysis - Yasmine Gamil; Mohamed G. Hamed; Mahitab Elsayed; Aya Essawy; Sara Medhat; Shaimaa O. Zayed; Radwa M. Ismail (BMC Oral Health, 2024)
Abstract Background Oral thrush is the most common occurring fungal infection in the oral cavity in uncontrolled diabetic patients, it is treated by various antifungal drugs according to each case. This study aimed to evaluate the therapeutic effects of topical application of miconazole and miconazole-loaded chitosan nanoparticles in treatment of diabetic patients with oral candidiasis. Methods In this randomized controlled clinical trial. A total of 80 diabetic patients presenting with symptomatic oral candidiasis were randomly assigned into two treatment groups: miconazole and miconazole-loaded chitosan nanoparticles. The patients were treated for 28 days, and clinical assessments were conducted at baseline, 7, 14, 21 and 28 days. Clinical parameters, including signs and symptoms of oral candidiasis were evaluated and microbiological analysis was performed to determine the Candida species and assess their susceptibility to the antifungal agents. Statistical analysis was done to the categorical and numerical data using chi-square test and Kruskal Wallis test. Results The antifungal efficacy between the miconazole and miconazole-loaded chitosan nanoparticles (CS-MCZ) groups insignificant difference (P >  0.05) was observed. Both treatment modalities exhibited comparable effectiveness in controlling oral candidiasis symptoms and reducing Candida colonization as miconazole-loaded chitosan nanoparticles group showed a significant difference in the clinical improvement in respect of both signs and symptoms from baseline (70%) until the end of study at 28 days (5%) (P <  0.05) Moreover, miconazole-loaded chitosan nanoparticles, there was a significant reduction in the number of colonies forming units of Candida albicans from baseline until the end of the study at 28-day with P value <  0.000. Conclusions This randomized controlled clinical trial and microbiological analysis demonstrate that both miconazole and miconazole-loaded chitosan nanoparticles are effective in the treatment of oral candidiasis in diabetic patients with no adverse reactions. Trial registration NCT06072716 with first registration first registration in 10/10/2023.